n(n-7)=

Simple and best practice solution for n(n-7)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for n(n-7)= equation:


Simplifying
n(n + -7) = 0

Reorder the terms:
n(-7 + n) = 0
(-7 * n + n * n) = 0
(-7n + n2) = 0

Solving
-7n + n2 = 0

Solving for variable 'n'.

Factor out the Greatest Common Factor (GCF), 'n'.
n(-7 + n) = 0

Subproblem 1

Set the factor 'n' equal to zero and attempt to solve: Simplifying n = 0 Solving n = 0 Move all terms containing n to the left, all other terms to the right. Simplifying n = 0

Subproblem 2

Set the factor '(-7 + n)' equal to zero and attempt to solve: Simplifying -7 + n = 0 Solving -7 + n = 0 Move all terms containing n to the left, all other terms to the right. Add '7' to each side of the equation. -7 + 7 + n = 0 + 7 Combine like terms: -7 + 7 = 0 0 + n = 0 + 7 n = 0 + 7 Combine like terms: 0 + 7 = 7 n = 7 Simplifying n = 7

Solution

n = {0, 7}

See similar equations:

| -2x-(x-2)=5x+3(x+1) | | -9+8s=8s-2 | | 3(2x+y)= | | duck+duck=wink | | 65y=32(2y+11) | | 13(x-3)=-6-7 | | .40+.70(100)=.60(100+x) | | 220x-x^2=0 | | 5(y-2)= | | 8/3=h/15 | | x+2=3-4 | | 2x+17=4x-13 | | 3g-3= | | -15x^2+1050x-9000=0 | | D-th=u | | 4t=-t+5t | | 5m(2m+3)= | | x^3y-3x^2y^2-40xy^3=0 | | x^8=656 | | y-x=0 | | 5y+8=20x+43 | | 0.9x-5.6=0.7 | | 12g-7=5 | | (x)(x)-2x-15=0 | | -4(t-3)+7t=8t-2 | | 5(5x-5)+3=25x-22 | | 3/8-m/9=7/72 | | -4x+3y+1=0 | | 2x+30=140 | | 3(5c-1)(-2)=13c+3 | | 2x+80=140 | | 8x+2=8(x-8) |

Equations solver categories